In Situ Synthesis of Manganese Oxide as an Oxygen‐Evolving Catalyst: A New Strategy. Issue 4 (10th November 2020) - Abdi, Zahra; Bagheri, Robabeh; Reza Mohammadi, Mohammad; Song, Zhenlun; Görlin, Mikaela; Dau, Holger; Najafpour, Mohammad Mahdi
Abstract: All studies on oxygen‐evolution reaction by Mn oxides in the presence of cerium(IV) ammonium nitrate (CAN) have been so far carried out by synthesizing Mn oxides in the first step. And then, followed by the investigation of the Mn oxides in the presence of oxidants for oxygen‐evolution reaction (OER). This paper presents a case study of a new and promising strategy for in situ catalyst synthesis by the adding Mn II to either CAN or KMnO4 /CAN solution, resulting in the formation of Mn‐based catalysts for OER. The catalysts were characterized by scanning electron microscopy, energy‐dispersive spectroscopy, transmission electron microscopy, X‐ray diffraction, Fourier transform infrared spectroscopy, X‐ray absorption spectroscopy, and X‐ray photoelectron spectroscopy. Both compounds contained nano‐sized particles that catalyzed OER in the presence of CAN. The turnover frequencies for both catalysts were 0.02 (mmol O 2 /molMn ⋅s). Abstract : The in situ formation of manganese oxide as an oxygen‐evolving catalyst in the presence of cerium(IV) ammonium nitrate was reported for the first time.